Pengaruh Penggunaan Microsoft Sway Sebagai Media Pembelajaran pada Mata Pelajaran Seni Budaya untuk Meningkatkan Hasil Belajar Siswa Kelas VIII di SMP IT Najib Rasyid (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve student learning outcomes in Cultural Arts subjects at Najib Rasyid IT Junior High School, considering that the conventional learning methods that have been used are less effective in the digital era. This improvement is sought through the application of Microsoft Sway interactive learning media as a teacher's tool in delivering material. This research uses quantitative methods with the type of Quasi Experiment and pretest-posttest control group design. The research sample consisted of 56 students, namely Class VIII B as the experimental class (28 students) and Class VIII C as the control class (28 students). Data were collected through observation, tests (questions), and questionnaires. The results showed that the application of Microsoft Sway interactive learning media successfully improved student learning outcomes in Cultural Arts subjects. Learning becomes more effective and relevant to the needs in the digital era.